Adaptive Behavior of College Students With Autism. (March 2022) - Viezel, Kathleen D.; Freer, Benjamin; Morgan, Chelsea D.
As an increasing number of individuals with autism spectrum disorder (ASD) matriculate on college campuses, all stakeholders should be prepared to meet their needs. Despite a body of literature describing adaptive behavior deficits of individuals with ASD, there is a paucity of research examining these skills among those who are college-ready. The present study investigated the adaptive behavior of a diverse group ( N = 27) of incoming college students with ASD and examined to what extent these skills could predict initial academic success. Despite average intelligence and good academic indicators, deficits in communication, socialization, and daily living skills were found. No models, even those that included intelligence quotient (IQ) and SAT scores, were predictive of first-semester or first-year grade point average (GPA). Importantly, freshman-to-sophomore retention appeared higher than the university average. Findings suggest that practitioners and families should consider adaptive behavior in addition to intellectual and academic capabilities when considering postsecondary opportunities and available supports.